D6.13 Report on the extroversion programme activities (update 1) - Hadjimitsis, Diofantos G.; Anayiotos, Andreas; Fotiou, Kyriaki; Panagiotou, Constantinos F.; Tzouvaras, Marios; Varvaris, Ioannis; Anastasiadou, Maria N.; Schreier, Gunter; Kaskara, Mariza; Salta, Fotini (My University, 2025)
This deliverable provides a comprehensive review of the extroversion-related actions undertaken during the 18-month period from Month 49 (October 2023) to Month 66 (March 2025) of the EXCELSIOR project implementation. The extroversion programme is designed to enhance the visibility, outreach, and strategic positioning of the ERATOSTHENES CoE, enabling it to address both regional and European challenges effectively. The programme's key objectives include: Expanding the knowledge and perspectives of ERATOSTHENES CoE’s staff through exposure to international best practices and emerging trends. Participating in global conferences, workshops, and networking events to shape ERATOSTHENES CoE’s strategic direction and foster collaborations. Conducting targeted training sessions and engaging in discussions with industry professionals to facilitate knowledge exchange and strengthen partnerships. This deliverable provides a detailed analysis of the activities carried out within this framework, evaluating their impact and contribution to the overall objectives of the EXCELSIOR project.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; Extroversion programme